Digital-Mediated Transformative Learning: A Mezirowan Perspective on Meaning Reconstruction in Arabic Language Education - Noor Zinatul Hamidah; Muassomah Muassomah; Raden Taufiqurrochman; Mohammad Shohibul Anwar; Rodiatul Maghfiroh (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to examine how digital media mediates the transformative learning process in Arabic language learning at MAN 1 Jember using the perspective of Jack Mezirow’s transformative learning theory. This study used a qualitative approach with a single-classroom case-study design and a descriptive-interpretive orientation. Data were collected through classroom observations, semi-structured interviews, and analysis of digital learning artifacts. The results show that digital media functions as an epistemic mediator, raising disorienting dilemmas, facilitating critical reflection, strengthening reflective dialogue, and supporting the reconstruction of students’ frames of reference. Digital mediation encourages a shift in students’ understanding of Arabic from a structural subject to contextual, social, and meaning-oriented language practices. Theoretically, this study enriches Mezirow’s framework by emphasizing the role of digital, multimodal cues in meaning reconstruction. Pedagogically, these findings provide a foundation for the development of digital-based Arabic language learning that is reflective and transformative.